Computador vestível afetivo co-evolutivo: processos de comunicação entre corpos biológico e tecnológico - Zuanon, Rachel (2007)
That theory has for objective to present to discuss of and a proposal makes vestível of co-evolutionary computer."" A practical application of this machine is to make possible processes of sensorial-motive communication enter in man-man man-machine of and, specifically a creation and execution of involuntary voluntary movements of and. A research of of that of importance they live in promoting other communication channel that transposes the extents and verbal visual. That process understands as operations of following: movements of the one of acquisition (or they make thought of a movement) they make user do computer; code of those movements in incentives sensorial-motors and transmission of those incentives for body of the they do do or of another interator. That of Pará, computer of that it is constituted by an intelligent surface that involves: for of electrodes a capture of signs mioelétricos and of cerebral signs they make user; for of electrodes a neuromuscular of electric of stimulation make interator and two technological systems of communication - associative of an and other evolutionary. Such a surface changes of color and in way, co-evoluíndo who of with one during of garment he interaction process enters in both. For of having Projected the use of an or two individuals, the computer opera that communication process enters in people dose or physically distant. In both cases the movements (thoughts of or) are sent a net of a body of for of other. When the effective technological system associative of it is, the thought or the own movement accomplished by the user do computer is transmitted so that the same interataror another connected to the net feels him/it as incentives sensorial-motors and to execute him/it integrally. Be of Or, in that instance that computer acts as a device of sensorial-motive communication projected especially for an affection of change they enter in separate from geographically of individuals. Already in the evolutionary instance, an information (thought of or of movement) accomplished by the user do codified computer of it is, learned developed of and any technological of system. Like this, incentives of the one received of they be and executed as movements differ of the introduced initial information any system, it passes of because a to exhibit new patterns that characterize process of the co-authorial enters in man-machine. Way of In that, the computer acts as a device for a communication of movements through a creative process in the one that colaborativo of and they enter an intelligence does man and of the machine. One classifies theoretical interdisciplinary it was adopted for a course of that of accomplishment: studies affectionate computation developed by saber Rosalind Picard; concepts and applications in it connects brain-computer and researches in stimulation electric neuromuscular accomplished by Alberto Cliquet Jr